The impact of a national program to eliminate lymphatic filariasis in selected Myanmar immigrant communities in Bangkok and Ranong Province, Thailand - Wichai Satimai (2018)
Some immigrants from Myanmar to Thailand have brought Wuchereria bancrofti infections with them, causing a community health problem for Thai citizens. The seroprevalence of bancroftian filariasis was detected in 438 and 512 Myanmar immigrants residing in Bangkok and Ranong Provinces, respectively, along with 81 Thai citizens living in Bangkok. The immunochromatograpy card test was positive in 5 Myanmar immigrants living in Bangkok and 1 living in Ranong for a prevalence of 0.63%. Antifilarial IgG4 antibodies were found in 21 Myanmar immigrants living in Bangkok and 14 living in Ranong for a prevalence of 3.68%. None of the samples from Thai citizens were positive with either test. These prevalence rates are lower than those observed between 2001 and 2005. The Thai mass drug administration program to eliminate lymphatic filariasis among Myanmar immigrants appears to be a successful public health strategy.